The existence of a bundled CT head in Bahasa Indonesian - Park, Dongwoo (Linguistic research, 2022)
Regarding the formation of Bahasa Indonesian wh-questions, two main approaches have been proposed - the VP-fronting approach and the wh-movement approach. In this paper, I point out that these two existing approaches cannot fully account for the peculiar property of Bahasa Indonesian multiple wh-questions whereby either the subject wh-phrase or the object wh-phrase can be extracted and located in the scope position. In order to capture this, I propose that this language has a bundled CT head, which contains the featural requirements of C and T at the same time, and that an example of it is the overt interrogative head yang. The existence of a bundled CT head is also supported by an intriguing property found in copular constructions that a wh-element replacing the referential DP can be located in the post-copular position, but not in the pre-copular position. Additionally, it is argued that the lack of the complementizer-trace effect in this language also indicates that this language does have a bundled CT head.